Assessment of the outcomes and stability after mandibular incisor extraction in orthodontic patients: A systematic review and meta-analysis - Rasiga Gandhi; Poornima Jnaneshwar; Keerthi Venkatesan; Davis Devasahayam; Krishnaraj Rajaram; Rajia Mohamed Azharudeen; Kavichithraa Jothy (Journal of Dental Research, Dental Clinics, Dental Prospects, 2023)
Background. This study assessed the stability of the outcomes after mandibular incisor extraction (MIE) using intercanine width and peer assessment rating (PAR) scores in orthodontic patients. Methods. PubMed, Cochrane Library, Science Direct, Google Scholar, Ovid, and SciELO were systematically searched without restrictions until August 2022. A risk of bias assessment was performed using Newcastle-Ottawa Scale (NOS). The Grading of Recommendations, Assessment, Development, and Evaluation tool was used to assess the quality of evidence. Random effects meta-analysis was performed using RevMan software. Results. Seven retrospective studies met the inclusion criteria and were included. Meta-analysis identified a statistically significant reduction in intercanine width with MIE after the retention period. The mean difference in post-retention changes concerning intercanine width (MD=0.14, 95% CI: -2.17–1.89; P<0.00001) was significantly higher in premolar extraction (PE) compared to incisor extraction and significantly less in non-extraction compared to incisor extraction (MD=0.72, 95% CI: -0.59–2.03; P<0.00001). Improvements in PAR scores from the start of treatment to the retention period indicated a high outcome standard (>70%) with MIE treatment, with no significant difference in the reduction percentage compared to premolar and non-extraction groups. Conclusion. With the existing retrospective studies of limited evidence, treatment outcomes with MIE were found to show good improvements in PAR scores. Some reduction in the intercanine width was evident after the retention period, which was observed even with the other two treatment modalities that were compared. Hence, with careful evaluation, MIE could be considered a valid treatment option.